Diversification of CD1 Molecules Shapes Lipid Antigen Selectivity. (2nd February 2021) - Paterson, Nicole M; Al-Zubieri, Hussein; Barber, Matthew F
Abstract: Molecular studies of host–pathogen evolution have largely focused on the consequences of variation at protein–protein interaction surfaces. The potential for other microbe-associated macromolecules to promote arms race dynamics with host factors remains unclear. The cluster of differentiation 1 (CD1) family of vertebrate cell surface receptors plays a crucial role in adaptive immunity through binding and presentation of lipid antigens to T-cells. Although CD1 proteins present a variety of endogenous and microbial lipids to various T-cell types, they are less diverse within vertebrate populations than the related major histocompatibility complex (MHC) molecules. We discovered that CD1 genes exhibit a high level of divergence between simian primate species, altering predicted lipid-binding properties and T-cell receptor interactions. These findings suggest that lipid–protein conflicts have shaped CD1 genetic variation during primate evolution. Consistent with this hypothesis, multiple primate CD1 family proteins exhibit signatures of repeated positive selection at surfaces impacting antigen presentation, binding pocket morphology, and T-cell receptor accessibility. Using a molecular modeling approach, we observe that interspecies variation as well as single mutations at rapidly-evolving sites in CD1a drastically alter predicted lipid binding and structural features of the T-cell recognition surface. We further show that alterations in both endogenous and microbial lipid-binding affinities influence the ability of CD1a to undergo antigen swapping required for T-cell activation. Together these findings establish lipid–protein interactions as a critical force of host–pathogen conflict and inform potential strategies for lipid-based vaccine development.